Central banking in Barbados : reflections and challenges - Codrington, Harold ed. (Central Bank of Barbados BridgetownBB, 1997)
Looks at the types of policies required for stable and sustainable growth. Focuses on how the Central Bank of Barbados developed its capabilities for achieving its objectives.